2008
DOI: 10.1088/0953-8984/20/24/244113
|View full text |Cite
|
Sign up to set email alerts
|

Glass-forming liquids: one or more ‘order’ parameters?

Abstract: Abstract. We first summarize the classical arguments that the vast majority of glass-forming liquids require more than one "order" parameter for their description. Critiques against this conventional wisdom are then presented, and it is argued that the matter deserves to be reconsidered in light of recent experimental developments. Out of the eight basic thermoviscoelastic frequencydependent response functions, there are generally three independent functions. For stochastic dynamics we show that there are only… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 45 publications
0
61
0
Order By: Relevance
“…Taken together, Eqs. (19), (20), and (9) thus imply that from a single reference point (ρ * , T * , U * , W * ) we have a prediction for (ρ, T, U, W ) on the isomorph to which the reference point belongs. Figure 4 demonstrated that in the WU phase diagram, isochores to a good approximation are straight lines with slope γ , i.e., that one can write W (ρ, T ) = W 0 (ρ) + γ (ρ)U (ρ, T ).…”
Section: B An Approximate Equation Of State For Generalized Lj Systemsmentioning
confidence: 98%
See 3 more Smart Citations
“…Taken together, Eqs. (19), (20), and (9) thus imply that from a single reference point (ρ * , T * , U * , W * ) we have a prediction for (ρ, T, U, W ) on the isomorph to which the reference point belongs. Figure 4 demonstrated that in the WU phase diagram, isochores to a good approximation are straight lines with slope γ , i.e., that one can write W (ρ, T ) = W 0 (ρ) + γ (ρ)U (ρ, T ).…”
Section: B An Approximate Equation Of State For Generalized Lj Systemsmentioning
confidence: 98%
“…(14) and (15), the entire isomorph to which this state point belongs is thus traced out in the WU phase diagram using Eqs. (19) and (20). Alternatively, given a collection of isomorphic state point generated, e.g., as described in Sec.…”
Section: A Parametric Description Of Isomorphsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a series of papers published last year, [1][2][3][4][5] we introduced the concept of strongly correlating liquids and demonstrated by computer simulations that this includes a large class of model liquids. Specifically, the fluctuations, which are in many cases strongly correlated, are those of the configurational parts of pressure and energy, i.e., the parts in addition to the ideal gas terms, coming from the interatomic forces.…”
Section: Introductionmentioning
confidence: 99%